Genomic diversity and antimicrobial resistance among non-typhoidal Salmonella associated with human disease in The Gambia. Issue 3 (18th March 2022) - Darboe, Saffiatou; Bradbury, Richard S.; Phelan, Jody; Kanteh, Abdoulie; Muhammad, Abdul-Khalie; Worwui, Archibald; Yang, Shangxin; Nwakanma, Davis; Perez-Sepulveda, Blanca; Kariuki, Samuel; Kwambana-Adams, Brenda; Antonio, Martin
Abstract : Non-typhoidal Salmonella associated with multidrug resistance cause invasive disease in sub-Saharan Africa. Specific lineages of serovars Typhimurium and Enteritidis have been implicated. Here we characterized the genomic diversity of 100 clinical non-typhoidal Salmonella collected from 93 patients in 2001 from the eastern, and in 2006–2018 from the western regions of The Gambia respectively. A total of 93 isolates (64 invasive, 23 gastroenteritis and six other sites) representing a single infection episode were phenotypically tested for antimicrobial susceptibility using the Kirby–Bauer disc diffusion technique. Whole genome sequencing of 100 isolates was performed using Illumina, and the reads were assembled and analysed using SPAdes. The Salmonella in Silico Typing Resource (SISTR) was used for serotyping. SNP differences among the 93 isolates were determined using Roary, and phylogenetic analysis was performed in the context of 495 African strains from the European Nucleotide Archive. Salmonella serovars Typhimurium (26/64; 30.6 %) and Enteritidis (13/64; 20.3 %) were associated with invasive disease, whilst other serovars were mainly responsible for gastroenteritis (17/23; 73.9 %). The presence of three major serovar Enteritidis clades was confirmed, including the invasive West African clade, which made up more than half (11/16; 68.8 %) of the genomes. Multidrug resistance was confined among the serovar Enteritidis West African clade. The presence of this epidemic virulent clade has potential for spread of resistance and thus important implications for systematic patient management. Surveillance and epidemiological investigations to inform control are warranted.